Three new species of Kerevata (Braconidae: Rogadinae: Clinocentrini) from mainland Papua New Guinea - Butcher, Buntika Areekul; Quicke, Donald L. J. (Zootaxa, 2014)
Three new species of the distinctive, cyclostome, braconid wasp genus Kerevata (viz. Kerevata jamesmayi sp. nov., K. clarksoni sp. nov. and K. hammondi sp. nov.) from Mt Wilhelm, Madang Province, Papua New Guinea are described and illustrated, and a key provided to enable their identification and separation from the only other species described to date, K. pacifica, from New Britain in the Bismark Archipelago off the S. E. coast of New Guinea. Characters used to differentiate Kerevata from the related Confusocentrus are modified.